CAROTID BODY TUMORS SURGERY: EXPERIENCE OF 13 CASES AT A TERTIARY CARE HOSPITAL - Ahsin Manzoor Bhatti (Army Medical College Rawalpindi, 2018)
Objective: To share five year experience and a half years with emphasis on some technical aspects which will help those managing such cases. Study Design: Descriptive case series. Place and Duration of Study: Combined Military Hospital Rawalpindi, from Jul 2010 to Dec 2015. Material and Methods: All cases of CBT presenting to our department from Jul 2010 to Dec 2015 were included in the study and analyzed. Results: A total of 13 patients were treated at our institute in the last 5 and half years. Average age of patients was 38.5 years with a range of 22-55 years. Male to female ratio was 1:6.5. Mean interval between symptoms onset and presentation was 38.7 ± 16 months. None of the tumors were bilateral or malignant. Two patients had type I tumor (15%), seven patients had tumor of type II (54%) and four (31%) patients underwent resection for type III tumor. Type I and Type II tumor was removed by simple excision. Three cases of type III tumor were managed by excision, use of temporary shunt and followed by reconstruction of internal carotid artery. One of the type III tumor was excised with ligation of internal carotid artery. There was no mortality or stroke, three patients with type III tumors had transient dysphagia; One of them had marginal mandibular nerve palsy as well. We used bipolar diathermy in all cases, Harmonic TM Scalpel (Ethicon Endo-Surgery) in three cases and LigaSureTM (Covidien Ltd, Dublin Republic of Ireland) in three cases. Use of newer energy sources made dissection less bloody, quick and easier. Conclusion: CBT are rare tumors. Surgical excision should be carefully planned and executed with the help of modern energy sources to avoid any serious complications.